Membangun Karakter Siswa Melalui Kepribadian, Bahasa, dan Norma Kesantunan Guru - Shilphy, Shilphy (Yayasan Insanulhaq, 2025)
Teachers play an important role in the learning process, which can affect students, so that the personality, language, and norms of teacher politeness need to be considered and implemented properly. This study aims to determine the ideal teacher's personality, language, and politeness norms to be implemented for students. This study uses qualitative research methods, while data collection techniques are carried out by exploring journals, books, and other information relevant to the study. The findings show that the ideal teacher personality to educate students is a teacher with a disciplined, honest, and fair personality. While the language used in teaching is a language that is in accordance with the language principles contained in the Qur’an, namely Qaulan sadida, Qaulan marufa, Qaulan baligho, Qaulan maysuro, Qaulan layyina, and Qaulan karima. Last, the teacher’s politeness norm is having SAFT competence (Sidiq, Amanah, Fathonah, and Tabligh).